Highly Conformationally Restricted Cyclopropane Tethers with Three‐Dimensional Structural Diversity Drastically Enhance the Cell Permeability of Cyclic Peptides. Issue 13 (27th December 2016) - Matsui, Kouhei; Kido, Yasuto; Watari, Ryosuke; Kashima, Yousuke; Yoshida, Yutaka; Shuto, Satoshi
Abstract: The conformation of cyclic peptides is closely related to their physicochemical and biological properties, but their rational design to obtain a conformation with the desired properties is difficult. Herein, we present a new strategy by using conformationally restricted cyclopropane tethers (CPTs) to control the conformation and improve the cell permeability of cyclic peptides regardless of the amino acid sequence. Newly designed cis ‐ or trans ‐CPTs with three‐dimensional structural diversity were introduced into a model cyclic peptide, and the relationship between the conformation of the cyclic peptides and their cell permeability was analyzed. Peptides containing a CPT exhibited conformational diversity due to the characteristic steric feature of cyclopropane, among which peptides containing a CPT, cis ‐NfCf had remarkably higher cell permeability than peptides containing other CPTs—even superior to that of cyclosporine A, a known permeable cyclic peptide. Abstract : Conformation analysis : A new strategy that can dramatically change the conformation and physicochemical properties of cyclic peptides having an alll ‐amino acid sequence by introducing only a cyclopropane tether (CPT) is presented. Particularly, the introduction of a cis ‐NfCf fixed a conformation suitable for passive transport and substantially improved the cell permeability of the model cyclic peptide (see scheme).